2014
DOI: 10.1021/ol502223u
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Crystal-to-Liquid Phase Transitions of Azobenzene Derivatives and Their Application in Photolithography Processes through a Solid–Liquid Patterning

Abstract: The direct and reversible transformation of matter between the solid and liquid phases by light at constant temperature is of great interest because of its potential applications in various manufacturing settings. We report a simple molecular design strategy for the phase transitions: azobenzenes having para-dialkoxy groups with a methyl group at the meta-position. The photolithography processes were demonstrated using the azobenzene as a photoresist in a single process combining development and etching of a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
159
4
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(172 citation statements)
references
References 31 publications
5
159
4
4
Order By: Relevance
“…[33][34][35][36] Introduction of pendant groups at the 2-or 3-position can reduce intermolecular π-π interactions and allow photoisomerization in the bulk state on the time scale of minutes. [28] Recent work has also suggested that lamellar or monolayer azobenzene morphologies facilitate fast photoisomerization, [26,27,37] presumably by providing increased molecular freedom. In our exfoliated monolayer system, rapid photoliquefaction is enabled by the presence of highly disordered and fluidic ODMS surrounding monolayers of crystalline azobenzene.…”
Section: Reversible Photoliquefaction and Photosolidification Of Silomentioning
confidence: 99%
See 1 more Smart Citation
“…[33][34][35][36] Introduction of pendant groups at the 2-or 3-position can reduce intermolecular π-π interactions and allow photoisomerization in the bulk state on the time scale of minutes. [28] Recent work has also suggested that lamellar or monolayer azobenzene morphologies facilitate fast photoisomerization, [26,27,37] presumably by providing increased molecular freedom. In our exfoliated monolayer system, rapid photoliquefaction is enabled by the presence of highly disordered and fluidic ODMS surrounding monolayers of crystalline azobenzene.…”
Section: Reversible Photoliquefaction and Photosolidification Of Silomentioning
confidence: 99%
“…[24,25] Furthermore, few examples have demonstrated the photocontrolled switching of liquid and solid phases in azobenzene materials. [26][27][28][29] Given the importance of molecular arrangement in photoresponsive materials, self-assembly strategies that facilitate ordering of functional motifs are prudent. Recently, we reported on the synthesis of a class of well-defined and discrete end-functionalized siloxane oligomers that form highly ordered multidomain nanomaterials with sub-5 nm periodicities.…”
mentioning
confidence: 99%
“…Previously, we have reported a molecular design criteria for the solid-liquid phase transition in rod-shaped azobenzenes and demonstrated to use an azobenzene as a photoresist [23]. Substitution of a methyl group at the 3-position to azobenzenes having para-dialkoxy groups ( Figure 1, AZ-OCn; n = 6, 10, 12) drastically altered the phase transition photoresponse compared to the azobenzenes possessing two methyl groups at the 3-and 3'-positions or no methyl groups.…”
Section: Introductionmentioning
confidence: 99%
“…The early work has reported that LCs incorporating azobenzene moiety exhibit trans-cis photoisomerization behavior upon UV-Visible (UV-Vis) light irradiation [23,24]. Figure 6 shows the UV-induced trans-cis isomerization of compound 2c.…”
Section: Uv-visible Spectramentioning
confidence: 99%